Green finance pilot reform and corporate green innovation - Wang, Huaiming; Du, Dongying; Tang, Xiaojian; Tsui, Stephanie (Frontiers in Environmental Science, 2023)
This study investigates the impact of the green finance pilot reform on corporate green innovation using the formation of the China Green Finance Pilot Reform in 2017 as a quasi-natural experiment. It shows that the green finance pilot reform increases corporate green innovation. Furthermore, by highlighting the differences between green enterprises and heavily polluting enterprises, it also shows that the positive relationship between the green finance pilot reform and corporate green innovation is more pronounced in green enterprises than in heavily polluting enterprises. The mechanism analysis shows that the green finance pilot reform mainly affects corporate green innovation by easing financing constraints and reducing financing costs. The heterogeneity analysis indicates that the positive relationship between the green finance pilot reform and corporate green innovation is more pronounced in non-state-owned enterprises and large-scale enterprises. As a result, the effect of the green finance pilot reform on corporate green innovation gives rise to certain green innovation incentives. It is thus necessary to optimise the external corporate governance environment by promoting the green finance pilot reform and further offers practical implications for corporate green innovation decision-making.